Mekanisme Pengawasan Halal Supply Chains di Pasar Tradisional Indonesia sebagai Upaya Perlindungan Konsumen (Studi Kasus: Komoditi Daging Ayam dan Sapi di Empat Pasar Tradisional Surabaya) - Arifin, Ah. Ali; Musafa’ah, Suqiyah; Pratikto, Muhammad Iqbal Surya; Basya, Maziyah Mazza; Malik, Rizki Azizah (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
The guarantee of halal food products is not limited to only semi-finished and finished food products, but also to raw materials consumed by Muslims, which in this research are chicken and beef commodities. This research aims to map the supply chain for chicken and beef commodities with the Halal supply chain concept in Indonesia by taking research samples at four traditional markets in Surabaya, namely Wonokromo Market, Balongsari Market, Kedurus Market and Pegirian Market. This mapping of the supply chain for chicken and meat commodities was carried out to determine any potential irregularities that occurred at each point and monitoring efforts to maintain Sharia compliance throughout the process. The research approach used in this research is qualitative research referring to Biklen's theory, namely starting from the Thesa (the concept and theory of the Halal Supply Chain) and the Antithesis (alleged deviations at each point in the Halal Supply Chain of chicken and beef commodities) which are then analyzed to form Synthesis (Results of analysis of the Halal Supply Chain concept in the chicken and beef commodity supply chain). The research results obtained are the process of tracing the chicken and beef supply chain starting from farms, livestock middlemen, slaughterhouses, traders in traditional markets until finally reaching the final consumer. In the supply chain process, risks of irregularities can be identified, namely the sale of tiren chickens, the feeding of dangerous substances to chickens and cattle, the slaughter of animals that do not comply with Sharia, and the sale of dedeh. Integrative supervision by the Animal Husbandry Service, MUI and the Consumer Protection Foundation is carried out to prevent the risk of deviations from the Halal Supply Chain for chicken and beef meat commodities in Indonesia.